Streptokinase Adverse Reactions: A Review of Iranian Literature - Ava Mansouri; Shima Tasharoie; Saeideh Javidee; Mona Kargar; Maryam Taghizadeh-ghehi; Molouk Hadjibabaie; Kheirollah Gholami (Research Center for Rational Use of Drugs (RCRUD), 2015)
Thrombolytic agents are among the medications that are used widely for the treatment of thromboembolic disorders and myocardial infarction (MI). Despite the world-wide availability of newer specific agents, streptokinase (SK) is still the most frequently used medication from this class in Iran. Hence we conducted this study to review the adverse reactions to this medication which were reported in the Iranian studies. We preformed this study by searching the English resources such as Pubmed, Google scholar and Scopus. Additionally, we searched Google scholar, Scientific Information Database, Magiran and IranMedex to cover Persian articles.We found 50 articles from the mentioned resources after deleting the duplicated records. Nineteen articles remained after implementing the inclusion and exclusion criteria. In most of the studies the indication for SK treatment was MI. Assessment of streptokinase ADRs was the main focus of 7 studies. The most frequent adverse drug reaction (ADR) was related to the cardiovascular system. Among them arrhythmia and hypotension were the most frequent ones. The second most prevalent ADR was bleeding followed by allergic reactions. In two studies only a single system ADR was studied: neurologic adverse effects and elevation in liver enzymes. Only very limited number of studies assessed the causality of the ADRs which made the interpretation of the results difficult. Among the associated factors that were assessed as risk factors of ADRs, age was the focus of 2 studies. The Iranian studies reported frequent ADRs similar to previous reports. However, due to the heterogeneity of the studies we could not describe the frequency and severity of reported ADRs in a more clear and precise conclusion.